2008
DOI: 10.1103/physrevd.78.022004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy deposited by cosmic-ray particles on interferometric gravitational wave detectors

Abstract: We investigated the noise of interferometric gravitational wave detectors due to heat energy deposited by cosmic-ray particles. We derived a general formula that describes the response of a mirror against a cosmic-ray passage. We found that there are differences in the comic-ray responses (the dependence of temperature and cosmic-ray track position) in cases of interferometric and resonant gravitational wave detectors. The power spectral density of vibrations caused by low-energy secondary muons is 100-times s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Laboratory scale research throughout the last several decades of the 20th century led to the construction of a worldwide network of kilometer scale interferometers (Abramovici et al, 1992;Lück et al, 2006;Acernese et al, 2008;Tatsumi, 2008;Abbott et al, 2009c).…”
mentioning
confidence: 99%
“…Laboratory scale research throughout the last several decades of the 20th century led to the construction of a worldwide network of kilometer scale interferometers (Abramovici et al, 1992;Lück et al, 2006;Acernese et al, 2008;Tatsumi, 2008;Abbott et al, 2009c).…”
mentioning
confidence: 99%
“…Weather conditions at LHO during O3 prevented the correlation between low humidity and high blip glitch rate from being observed as suggested in [80,81]. Low energy cosmic rays striking the LIGO mirrors are responsible for a minute amount of noise in the interferometers [82,83]. High energy cosmic rays could cause blip glitches by strongly perturbing the detector's mirrors.…”
Section: Blipsmentioning
confidence: 99%
“…Gravitational-wave detectors are extremely sensitive to tiny vibrations and were shown to be able to detect comic-ray showers [398]. They can thus also be used to search for SMPs that would induce vibrations, such as monopoles and nuclearites [399,400].…”
Section: Gravitational-wave Detectors and Acoustic Sensorsmentioning
confidence: 99%
“…They can thus also be used to search for SMPs that would induce vibrations, such as monopoles and nuclearites [399,400]. In a study comparing the suitability of different kinds of gravitational-wave detectors for SMP detection, it was shown that resonant-bar detectors should be 30 − 300 times more sensitive than interferometers, due to a larger volume and a higher efficiency [398]. Searches performed at sea level using resonant-bar detectors quoted nuclearite flux limits at the level of 10 −12 cm −2 sr −1 s −1 for nuclearite masses M 10 11 GeV [401][402][403].…”
Section: Gravitational-wave Detectors and Acoustic Sensorsmentioning
confidence: 99%